2019
DOI: 10.1016/j.jaad.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the landscape of core outcome set development in dermatology

Abstract:  CS-COUSIN provides methodological support for dermatology-specific core outcome set initiatives to ensure high quality across core outcome sets in dermatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
(41 reference statements)
0
49
0
Order By: Relevance
“…Moreover, standardization of outcome measures is imperative for enabling comparisons between studies. Increased awareness of the importance of (high-quality) outcome measures has led to a rise in outcome measure research, especially in dermatology [13] (in particular for psoriasis [14], atopic dermatitis [15], and more recently vitiligo [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, standardization of outcome measures is imperative for enabling comparisons between studies. Increased awareness of the importance of (high-quality) outcome measures has led to a rise in outcome measure research, especially in dermatology [13] (in particular for psoriasis [14], atopic dermatitis [15], and more recently vitiligo [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is only possible to generalise towards this. However, previous literature has identified similar barriers to COS uptake for osteoarthritis, 13 sepsis, 14 and dermatology 15 trials. Third, pre-survey work based on Smith et al’.s 7 COS uptake analysis and piloting of this study’s survey suggested that awareness of the COS may be a major reason for non-adoption.…”
Section: Discussionmentioning
confidence: 83%
“…In 2016 the International Consortium for Health Outcomes Measurement (ICHOM) published a standard set of outcome measures to evaluate value in maternity care [12]. Standard sets are the same as core outcome sets but have a clear focus on clinical practice [13]. An ICHOM working party comprising two consumers and nineteen international experts convened to identify outcomes and measurement instruments for inclusion in their set [14].…”
Section: Introductionmentioning
confidence: 99%